Ontological foundations of moral culture. Part II - Morozov, Andrii; Shapovalov, Vladyslav; Hudkov, Serhii (Ukrainian Cultural Studies, 2024)
Background. Forgetting the problems of being, erasing the idea of being from the worldview of contemporary humans, and focusing on individualistic and hedonistic practices lead to the narrowing of the personality's fullness, dehumanization of its moral and spiritual dimension, and alienation from one's own essence. The ontological turn of thinking, turn to its essential foundations, will allow finding a reliable foundation for a moral culture shaken by skepticism and nihilism, and making an existential turn in search of a person's lost essence. The article is aimed to study the ontological foundations of moral culture. The task of the article's first part is to investigate the ontological framework of moral culture – its fundamental axes; the task of the article's second part is to analyze the moral concepts of freedom, conscience, dignity, and equality through the prism of the ontological framework. Methods. The article uses a historical-philosophical and comparative method, as well as methods of genealogy and hermeneutic methods of interpretation. The general research paradigm is the transcendental anti-positivist tradition of philosophizing. Results. It is argued that the parameters of reality and its internal structure are determined by the ontological framework, namely the axes of sacred and profane, single and multiple, phenomenal and essential (proper). The fundamental connection between the ethical and the ontological, in which human existence is always a moral existence, is emphasized. Moral culture, our ideas about good and evil depend on our understanding of existence. Moral concepts are ontological – point to an objective valuable reality, "material a priori". It is noted that ontological dignity includes formal and material (content) aspects, assuming the existence of ontological equality of all people, ontological freedom and ontological conscience. Conclusions. The vision of existence as a sacred gift enables the ontological dignity of a person, that is, his non-alienated transcendental self-being. The vision of the sacred gift of being in the unity of diversity, in turn, implies the vision of the ontological equality of all people, who, being different, are simultaneously equal as they are all gifted with being. The ontological equality of people requires a certain "common denominator" of humanity, which may vary depending on the chosen paradigm. A meaningful expression of ontological dignity is ontological freedom, which consists of a person's ability to say a transcendental "yes" or "no" to the world, and to choose between being-centric and egocentric modes of existence. Awareness of the two poles of existence – the essential and the phenomenal – gives rise to an ontological conscience: an individual's anxiety about the authenticity of one's own existence and guilt for not being oneself.
Keywords: ontological framework; ontological common denominator; existence as a sacred gift; ontological equality; ontological dignity; ontological freedom; ontological conscience; transcendental homeland